‘Usyur Dan Jizyah Dalam Kajian Ekonomi Islam - Hidayati, Nurul (TAWAZUN: Journal of Sharia Economic Law, 2018)
Fiscal policy is a policy pursued by the government in managing state income and expenditure. The state of Medina which was led by Muhammad SAW also had a unique fiscal policy system in his day. The implementation of fiscal policy at the time of the Prophet Muhammad and Abu Bakr was almost the same, because there were not many problems that emerged along with the expansion of the territory of the Islamic Caliphate. Sources of state revenues in the early days of Islam included the zakat, khums, jizyah, fai, ‘usyūr and other sources of income. One of the state revenues in the early days of Islam was ‘usyūr and jizyah. The discussion of 'usyur revolves around the definition, who is obliged to pay ‘usyūr, the item affected by‘ usyūr, the time of collection ‘usyūr, and the amount of levies. As for jizyah, the discussion revolves around the definition, the jizyah payer, the large number of levies, the termination of jizyah, the rights and obligations of Ahlu Zhimmah, the use of jizyah, orientalist criticism of jizyah, and then analyzing both. The policies exemplified by the Prophet Muhammad both legal, political and economic issues became guidelines for the Khulafa ar-Rashidin, his tireless friends always accompanied him. Among the policies relating to the economy are the collection of usyūr and jizyah. ‘Usyūr and jizyah are one of the sources of income at the beginning of Islam which is quite important for state finance. This policy is also used by followers in managing the economic life of the country.